2019
DOI: 10.1093/rfs/hhz046
|View full text |Cite
|
Sign up to set email alerts
|

Bank-Branch Supply, Financial Inclusion, and Wealth Accumulation

Abstract: This paper studies how financial inclusion affects wealth accumulation. Exploiting the U.S. interstate branching deregulation between 1994 and 2005, we find that an exogenous expansion of bank branches increases low-income household financial inclusion. We then show that financial inclusion fosters household wealth accumulation. Relative to their unbanked counterparts, banked households accumulate assets in interest-bearing accounts, invest more in durable assets, such as vehicles, have a better access to debt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(79 citation statements)
references
References 57 publications
3
60
0
1
Order By: Relevance
“…This corroborates with the study reported in [24]. Célerier and Matray in [26] did a study on the effects of FI on wealth accumulation in the context of USA. The authors studied the USA interstate branching deregulation policy between 1994 and 2005 and established that expansion of the bank branches across the states helped to increase access to funds the low-income earners, hence it increase the lowincome household FI.…”
Section: Related Worksupporting
confidence: 92%
See 1 more Smart Citation
“…This corroborates with the study reported in [24]. Célerier and Matray in [26] did a study on the effects of FI on wealth accumulation in the context of USA. The authors studied the USA interstate branching deregulation policy between 1994 and 2005 and established that expansion of the bank branches across the states helped to increase access to funds the low-income earners, hence it increase the lowincome household FI.…”
Section: Related Worksupporting
confidence: 92%
“…Presently in Africa there is so much interest to promote financial inclusion based on the commitment of so many countries to financial inclusion action plan to reduce poverty and grow their economy [26,30]. But Africa as a continent is lagging behind other continents in financial inclusion because inclusive development is left out [5,31].…”
Section: Resultsmentioning
confidence: 99%
“…Some hypothesize that this is due to a lack of access to low-cost, convenient savings devices at formal financial institutions (Karlan, Ratan and Zinman, 2014). When households do have access to financial institutions, there are a number of well-documented causal impacts including increased entrepreneurial investment, wealth accumulation, and ability to cope with shocks (Bruhn and Love, 2014;Stein and Yannelis, 2019;Célérier and Matray, forthcoming).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if search costs are a primary reason that many workers are not already saving for retirement, the introduction of an automaticenrollment retirement savings plan is likely to result in high participation rates at the default saving rate and significant incremental retirement savings. Evidence in Célerier and Matray (2019) that increased bank branch supply leads to greater wealth and net-worth accumulation in low-income households implies that supply-side solutions to low savings rates, such as OregonSaves, may lead to improved welfare.…”
Section: Introductionmentioning
confidence: 99%